Public Communication Strategy in Increasing Community Involvement in Central Java - Putra, Muhammad Amril Pratama; Rusdi, Muhammad (Universitas Muhammadiyah Makassar, 2023)
The role of public communication is of utmost significance in changing the dynamics of society, encompassing social, political, and economic aspects. This research analyzes the public communication strategy through social media, particularly Twitter, conducted by Ganjar Pranowo, the Governor of Central Java. The research method used in this study is content analysis with social media. Hashtags, as a key element in the communication strategy, play an important role in building a positive image of Central Java. Hashtag analysis reveals Ganjar Pranowo's focus on promoting comfort, infrastructure and handling COVID-19 in his region. Interaction patterns with official government and media accounts show strong collaboration in disseminating transparent information and increasing public engagement. Governor Ganjar Pranowo's active engagement on social media reflects an effective strategy to build trust and increase public engagement in modern governance. The results of this study provide insights into the potential and role of social media in strengthening public communication in the realm of government.